Water quality assessment of river at Universiti Teknologi Malaysia - Chang, Shiang Yi, 1989-, author; Azmi Aris, supervisor; Fakulti Kejuruteraan Awam (2014)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Alam Sekitar)) - Universiti Teknologi Malaysia, 2014